Teacher's Strategy in Online Learning in English Courses at SMP Al-Afkari Deli Serdang: Strategi guru dalam pembelajaran daring pada mata pelajaran Bahasa Inggris di SMP Al-Afkari Deli Serdang - Pasaribu, Gumarpi Rahis; Sidabutar, Usman (Journal of Literature and Education, 2023)
The aims of this research are to identify and describe the challenges faced by the English teachers in online teaching at SMP Al-Afkari Deliserdang. It is then to analyze and classify the strategies used by the English teachers in online teaching at SMP Al-Afkari Deliserdang. The type of this research was phenomenological research with a qualitative approach. This study uses theory of Wehrli & Nyquist (2003). In collecting the data, observation, interview, and documentation were applied. The results showed that: first, the challenges faced by the English teacher in online teaching, namely internet connection, media, limited internet package, students' learning interest and extra supervisions of students. Second, the strategies used by the English teachers in online teaching at SMP Al-Afkari Deliserdang namely: brainstorming, questions and answers, independent study, self-awareness exercise/test, lecture/presentation, and demonstration.